Air temperature data from the Serra da Estrela (Central Portugal) from January to December 2000 - Mora, Carla (PANGAEA, 2018)
The Serra da Estrela is part of the Iberian central cordillera and is the highest mountain in mainland Portugal (40º20'N, 35 W, 1993 m a.s.l). Seven air temperature data loggers were installed in contrasting topographic positions, with special focus on valley floors and interfluve sites to study topoclimatology. Data collection was made at 2-hour intervals during 2000 using Tiny Talk II single-channel 8-bit dataloggers with a 2K EEPROM memory. The air temperature monitoring device was constructed using a specially designed solar radiation shield based on white painted PVC tubes installed at 130 cm above the ground surface. The system is described in Vieira et al. (2000).